Upregulation of Phospholipase D Expression and Activation in Ventricular Pressure-Overload Hypertrophy - Ali A. Peivandi; Alexander Huhn; Hans-Anton Lehr; Shenchu Jin; Joachim Troost; Sonia Salha; Tobias Weismüller; Konrad Löffelholz (Elsevier, 2005)
Evidence for a role of phospholipase D (PLD) in cellular proliferation and differentiation is accumulating. We studied PLD activity and expression in normal and hypertrophic rat and human hearts. In rat heart, abdominal aortic banding (constriction to 50% of original lumen) caused hypertrophy in the left ventricle (as shown by weight index and ANP expression) by about 15% after 30 days without histological evidence of fibrosis or signs of decompensation and in the right ventricle after 100 days. The hypertrophy was accompanied by small increases of basal PLD activity and strong potentiation of stimulated PLD activity caused by 4β-phorbol-12β,13α-dibutyrate (PDB) and by phenylephrine. The mRNA expressions of both PLD1 and PLD2 determined by semiquantitative competitive RT-PCR were markedly enhanced after aortic banding. In the caveolar fraction of the rat heart, PLD2 protein determined by Western blot analysis was upregulated in parallel with the expression of caveolin-3. A similar induction of PLD mRNA and protein expression was observed in hypertrophied human hearts of individuals (39 - 45-year-old) who had died from non-cardiac causes. In conclusion, PLD1 and PLD2 expressions were strongly enhanced both in rat and human heart hypertrophy, which may be responsible for the coincident potentiation of the PLD activation by α-adrenoceptor and protein kinase C stimulation. These results are compatible with a significant role of PLD activation in cell signaling of ventricular pressure-overload hypertrophy. Keywords:: cardiac hypertrophy, signal transduction, phospholipase D, protein kinase C, α-adrenoceptor